PERADABAN ISLAM MASA KHALIFAH UMAR IBN AL-KHATHTHAB (13-23 H/634-644 M) - Latifa Annum Dalimunthe (FORUM PAEDAGOGIK, 2018)
Abu Bakr appointed Umar ibn khaththab to be caliph to avoid divisions among Muslims. Umar was born in 513 A D into a family of the Quraish tribe. At first he was called by the title Abu Hafs, and after converting to Islam he received the title al-Faruq and was most persistent in defending Islam. This research examines how the Islamic civilization in Umar's era. The research was conducted by taking a literature study from the literature books. The results showed that Umar's leadership included the territory of the Arabian Peninsula.Palestine, Syria, Iraq, Persia, and Egypt. Umar formed departments (diwan) such as the police, baitul mal to manage state finances. Umar succeeded in restoring the stability of the Islamic government and even strengthening the country. Umar died of a sharp knife stabbed by Abu Lu'luah or Fairuz who was going to offer the dawn prayer at the Nabawi mosque.